2004
DOI: 10.1111/j.0141-9889.2004.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical modernisation, scientific research fields and the epistemic politics of health social movements

Abstract: As health social movements (HSMs) and complementary and alternative medicine (CAM) professions increasingly mount challenges to the authority of medical knowledge, the tendency for the medical research community and medical profession to dismiss such epistemic challenges (termed here 'paternalistic progressivism') and the corresponding response from challengers that medicine is corrupt (termed here 'medical devolution') has given way to a process of incorporation of challenges under the rubric of evidence-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 23 publications
0
65
0
1
Order By: Relevance
“…It appears that in this case, this boundary was distinctly porous as scientists felt compelled to intercede in medical education. Previous studies of boundary work in CAM have shown that medical professionals have followed a policy of expanding their practice to incorporate selected aspects of CAM (Adams, 2005, Hess 2004). However, this study demonstrates that Colquhoun and supporters instead sought to expel CAM, and homeopathy in particular, from both medicine and science.…”
Section: Resultsmentioning
confidence: 99%
“…It appears that in this case, this boundary was distinctly porous as scientists felt compelled to intercede in medical education. Previous studies of boundary work in CAM have shown that medical professionals have followed a policy of expanding their practice to incorporate selected aspects of CAM (Adams, 2005, Hess 2004). However, this study demonstrates that Colquhoun and supporters instead sought to expel CAM, and homeopathy in particular, from both medicine and science.…”
Section: Resultsmentioning
confidence: 99%
“…Research projects were set up on a larger scale, collaborations between several disciplines were established and 'society began to talk back to science' (Barry, 2001;Hess, 2004;Tupasela, 2007). These developments occurred in the Netherlands later in psychiatry than elsewhere in medicine.…”
Section: Starting To Conduct Psychiatric Genomics Research: On Hypothmentioning
confidence: 99%
“…However, because it largely restricts its analyses to autonomous scientific fields in which activists are forced to conform to scientific epistemic standards so as to portray themselves as credible knowers (see Epstein 1996), it overlooks their role in fundamental epistemological debates. In less autonomous fields, like medicine, or in fields experiencing epistemological flux, social movements like homeopathy can engage in "knowledge advocacy" on fundamental epistemological grounds (Whooley 2008), offering "epistemic challenges" as they are less pressed to debate the issues on the field's own terms (Hess 2004).…”
Section: Resultsmentioning
confidence: 99%